The origin, history, and resistance architecture of an invasive urban malaria mosquito in Africa - Tristan P. W. Dennis; Jihad Eltaher Sulieman; Mujahid Nouredayem; Temesgen Ashine; Yehenew Ebstie; Adane Eyasu; Eba A. Simma; Endalew Zemene; Nigatu Negash; Abena Yigeremu; Muluken Assefa; Hamza Elzack; et al. (Science, 2026)
The invasive urban malaria vector Anopheles stephensi threatens 126 million city dwellers in Africa. Controlling An. stephensi requires greater understanding of its origin, invasion dynamics, and insecticide resistance mechanisms. Analysis of 645 whole genomes sampled across Africa, the Middle East, and Asia supports an invasion scenario in which an initial South Asian introduction established a bridgehead population in Djibouti, which seeded distinct invasion fronts in Sudan, Ethiopia/Kenya, and Yemen. These incursions show contrasting rates and routes of spread shaped by landscape topology. Insecticide resistance is predominantly mediated by metabolic detoxification genes, with resistance haplotypes and copy-number amplifications introduced from South Asia. These findings, alongside a companion genomic resource, enable genomic surveillance of An. stephensi spread and resistance to aid control strategies.